Changing Academic Roles - Hovenga, E. J. S.; Bricknell, L. (Methods of Information in Medicine, 2006)
Objectives: A primary objective of this study was to identify a valid method for academic workload allocation. This required the identification of significant variables that may be used to indicate and measure academic workload. A supporting objective was to illustrate how the adoption of a flexible learning mode and supporting technologies across one university with multiple campuses and an international student cohort has impacted upon academic roles and teaching delivery methods.Methods: An extensive literature review focusing primarily on the teaching aspects of academic roles was undertaken. These roles were defined as teaching, including curriculum development, undertaking research, provide professional and community services and undertake some administrative work. This review was followed by the documentation of a case study.Results: Significant changes to the roles and responsibilities of academics working in higher education are now discernable. The adoption of Web-based applications and other communication technologies have made it possible to not only extend traditional distance education offerings but also to teach large multicultural classes across multiple campuses simultaneously. This in turn necessitates a review of teaching strategies and of organization-wide student and staff support infrastructures to ensure that the teaching quality is maintained or improved whilst meeting individual student learning needs.Conclusions: Changes to academics’ roles are occurring due to the globalisation of higher education as well as the adoption of new educational delivery methods and the use of new technologies. The resulting complexity of academic workload measurement and the need to equitably allocate this workload to individual academics has become more challenging than ever. More traditional universities can learn from such experiences to better prepare for these inevitable changes.
Keywords: Academic workload; distance learning; teaching; learning